Mediating Role of Self-Efficacy in the Relationship Between Optimism, Psychological Well-Being, and Resilience Among Iranian Students - Sabouripour, Fatemeh; Roslan, Samsilah; Ghiami, Zeinab; Memon, Mumtaz Ali (Frontiers in Psychology, 2021)
The present study aimed to examine whether self-efficacy mediates the relationship between optimism, dimensions of psychological well-being (PWD), and resilience among Iranian students. The participants in this study included 251 Iranian students from University Putra Malaysia (UPM). Structural equation modeling using AMOS 20.0 was used to analyze the data. The results indicated that there are significant relationships between optimism, dimensions of psychological well-being, and resilience among Iranian students of UPM. The study findings presented that self-efficacy mediates the relationship between dimensions of psychological well-being (environmental mastery, autonomy, self-acceptance, positive relations with others, personal growth, and purpose in life) and resilience among Iranian students of UPM. Further, it found that self-efficacy does not mediate the influence of optimism on resilience among Iranian students of UPM. The study's finding helps to understand the connection mechanism of self-efficacy, various dimensions of psychological well-being, and resilience. The result could help counselors, psychologists, and instructors develop and plan valuable strategies to enhance students' psychological factors.